Interleukin-8 (IL-8) levels in gingival crevicular fluid during root canal treatment of molar teeth with symptomatic irreversible pulpitis: impact of varying sodium hypochlorite concentrations - Esin Özlek; Gizem Kadı; Nasser Shoshaa; Yusuf Saed; İsmet Meydan (BMC, 2024)
Abstract Background The aim of this study was to evaluate the effect of the use of different NaOCl concentrations (1%, 2.5%, and 5.25%) during root canal treatment of molar teeth with symptomatic irreversible pulpitis on the change of the IL-8 level in gingival crevicular fluid (GFC). Methods GCF sampling was performed on experimental tooth with irreversible pulpitis before and after treatment and also contralateral healthy tooth of 54 patients. The patients were divided into three groups according to concentration of NaOCl solution (n = 18); 1%, 2.5%, and 5.25% NaOCl solution. GCF sampling from experimental teeth was repeated one week after root canal treatment. Statistical analysis was performed using Mann-Whitney U, Wilcoxon test, one-way ANOVA and Pearson correlation analysis. Results There was a significant correlation between IL-8 levels in GCF samples taken from teeth with pulpitis before treatment and from healthy contralateral teeth (p = .000). Furthermore, the pretreatment IL-8 level was significantly higher than the posttreatment IL-8 level(p < .05). The effect of the NaOCl concentration on the change in IL-8 level betweeen pre and post treatment was not found statistically significant (p > .05). Conclusions The use of NaOCl during root canal treatment can effectively reduce the levels of IL-8 in GCF and improve clinical outcomes. Trial registration This study was registred in the Institutional Review Board and the Ethics Committee of the University (No:11) on 15/12/2021.